Hybrid-production model for long-term forecasting of economic growth - Kovalev, Mikhail M.; Gospodarik, Catherine G. (Journal of the Belarusian State University. Economics, 2018)
The article analyses the approaches to the long-term projection of economic growth and its factors (labour, capital and total factor productivity) in the Republic of Belarus by 2050. The authors apply the idea of hybrid approach using production functions in order to forecast the economic growth by 2050 and compare their results with world well-known forecasting institutions. All forecasts of foreign centers are summarized in the consensus forecast. The potential growth of the Belarusian economy according to the hybrid model is quite significant, even considering the bad starting conditions of the last three years.
Keywords: forecasting; economic growth; long-term projection; labour and human capital; GDP growth; total factor productivity; capital forecasting